Infrared Thermal Imaging in Patients with Medial Collateral Ligament Injury of the Knee - A Retrospective Study - HyunJung Yang; HaeIn Park; Chungsan Lim; SangKyun Park; KwangHo Lee (Korean Pharmacopuncture Institute, 2014)
Objectives: Digital infrared thermographic imaging (DITI) has been used widely for various inflammatory diseases, circulatory diseases, skin diseases, musculoskeletal diseases and cancers. In cases of ligament injury, obviously the temperature of the damaged area increases due to local inflammation; however, whether the temperature also increases due to DITI has not been determined. The purpose of the present study was to identify whether or not the changes of temperature in patient's with medial collateral ligament injury were really due to infrared thermography and to determine the applicability of DITI for assessing ligament injuries. Methods: Twenty patient's who underwent DITI for a medial collateral ligament injury from September 2012 to June 2014 were included in the current study. The thermographic images from the patient's knees were divided to cover seven sub-areas: the middle of the patella, and the inferomedial, the inferolateral, the superomedial, the superolateral, the medial, and the lateral regions of patella. The temperatures of the seven regions were measured, and the temperature differences between affected and unaffected regions were analyzed by using the Wilcoxon signed rank test. Results: The 20 patient's were composed of 14 women (70%) and 6 men (30%), with a mean age of 62.15 ± 15.71 (mean ± standard deviation (SD)) years. The temperature of the affected side, which included the middle of the patella, and the inferomedial, the superomedial, the superolateral, and the medial regions, showed a significant increase compared to that of the unaffected side (P < 0.05). The inferolateral and the lateral regions showed no significant changes. Conclusion: Our study results suggest that DITI can show temperature changes if a patient has a ligament injury and that it can be applied in the evaluation of a medial collateral ligament injury.